SOSIALISASI PENGGUNAAN MEDIA SOSIAL YANG AMAN DARI BAHAYA PHISHING DAN HOAX DI MTS. MATHLA'UL ANWAR - Nurfiqih; Aa. Kurniawan (Abdi Jurnal Publikasi, 2025)
The threat of phishing and hoax-related cybercrimes spreading through social media platforms is becoming increasingly prevalent due to irresponsible individuals. Phishing is a fraudulent technique used to steal personal information, such as login credentials and financial data, by impersonating trusted entities. Meanwhile, hoax involve the spread of false information that can mislead the public and cause various negative impacts, such as panic, hatred, or manipulation of public opinion. Therefore, preventive measures are essential to protect individuals from potential cyberattacks. One such effort was carried out through a socialization activity on safe and wise use of social media at Madrasah Tsanawiyah Mathla'ul Anwar. The primary goal was to educate and raise awareness among students about the dangers of phishing and hoaxes, so they can engage more responsibly online. The activity involved 25 participants and employed lecture and discussion methods. The results of the socialization showed a highly positive response from the participants. Based on a questionnaire distributed after the session, 32% of participants rated the activity as